Effect of some species of bacteria on viability of human hydatid cysts (Baghdad Science Journal, 2025)
A total of 50 fertile human hydatid cases {33(66%) females and (34%) males}, obtained from Al-Ramadi public Hospital during the period from December 2003 to July 2004 were examined to study any bacterial infections. The specimens were obtained from hydatid fluid and then cultured on appropriate culture media to distinguish some species of bacteria which resulted in obtaining: Staphylococcus aureus (18%), Pseudomonas aeruginosa(12%), Escherichia coli(6%) and Streptococcus pneumonia (4%). These bacteria were confirmed by isolation from interacyst fluid and blood culture technique. The possible routs of infection may be through blood, biliary ducts and bronchioles .The selectivity permeable of the cyst wall may be absent and that may allow some species of bacteria to enter inside the cyst. Further, the percent viability decreased among cyst which yielded S. aureus , P. aeruginosa and other bacteria isolated after culturing compared with those of negative culture .Besides, the two types of protoscoleces motilities (flame cell activity and constriction –relaxation movement )increased in cases of negative culture .This association holds true at three different temperature (25ºC,37ºC and 40ºC).